Réseaux traditionalistes catholiques et « réinformation » sur le web : mobilisations contre le « Mariage pour tous » et « pro-vie » - Charlotte BLANC (Tic & Société)
Catholic traditionalist networks and re-information on the web: Same-sex marriage and pro-life mobilizations – This article deals with traditional Catholicism networks on the web. It seeks to bring a new perspective into studies of Catholic militantism, especially regarding the theme of family. The article deals with anti-gay marriage and pro-life mobilisations on the Catholic blogosphere. It also questions the rise of a set of ideologically oriented blogs, called ‘‘reinfosphere’’, and their roles in Catholic mobilisation.